The application of integrating medical humanities education into emergency skill-training scenario simulation teaching - Guo, Hongkun; Li, Huan; Yao, Yongdong; Li, Yiming; Huang, Yanjing (Frontiers in Medicine, 2025)
ObjectiveTo explore the value of integrating medical humanities education into emergency skill training scenario simulation teaching.Method69 first-year professional master’s students studying at Fujian Medical University(China) were selected as research subjects. They were randomly divided into control (n = 39) and observation (n = 40) groups. All students received emergency skills training. The control group adopted the scenario simulation teaching method, while the observation group integrated medical humanities education based on the control group. Assessment scores and satisfaction with the teaching mode were compared between the two groups.ResultsThe observation group outperformed the control group in practical, theoretical, and comprehensive grades, and were more satisfied with the teaching mode, with both differences being statistically significant (p < 0.05).ConclusionIncorporating medical humanities education into emergency training simulations can enhance teaching quality, boost students’ ethical literacy, and improve teaching satisfaction, making it worthy of widespread application.